The Effect Of Audit Tenure, Company Size, Audit Firm's Reputation On Audit Quality - Nasuci, Kinanti Putri; Sari, Retna; Sari, Ratna Hindria Dyah Pita (Institut Bisnis dan Informatika Kesatuan, 2020)
This study aims to determine the effect of audit tenure, company size, and KAP's reputation on audit quality. The theory used in this research is agency theory. This research used quantitative research method. This data collected was secondary data by documentation and literature study. The sample used in this study was manufacturing companies in the consumer goods sector which were listed on the Indonesia Stock Exchange in 2015 – 2018. The sample of this study amounted to 128 observational data from 32 companies chosen by purposive sampling method. The analysis used logistic regression analysis. The results showed audit tenure and KAP's reputation have a significant effect on audit quality, while firm size has no significantly effect on audit quality. Keywords: Audit Quality, Audit Tenure, Company Size, KAP Reputation